Вторая палатализация в западно-мерсийском диалекте древнеанглийского языка - Армалите, О. (Kalbotyra, 1976)
The second fronting, a prominent feature of the West Mercian dialect, consisted of two changes: raising of the reflexes of Pr OE /æ̌1/ and fronting of Pr OE /ă/. The raising of Pr OE /æ̌1/in the West Mercian dialect resulted in the emergence of a new mid-low front unrounded phoneme /ɛ̌/. The analysis of the orthography of West Mercian writings allows us to conclude that the two changes were not quite simultaneous as has been the traditional point of view. The raising of Pr OE /æ̌1/ must have preceded the fronting of /ă/ and is to he placed back in the early period (presumably prior to i-umlaut). The fronting of /ă/, a later development, belongs to the period before back umlaut.